Ensuring Mobility-Supporting Environments for an Aging Population: Critical Actors and Collaborations - Chris S. Kochtitzky; Amy L. Freeland; Irene H. Yen (Journal of Aging Research)
Successful aging takes on an array of attributes, including optimal health and community participation. Research indicates that (1) persons with disabilities, including age-related disabilities, report frequent barriers to community participation, including unsuitable building design (43%), transportation (32%), and sidewalks/curbs (31%), and (2) many seniors report an inability to cross roads safely near their homes. This paper attempts to define mobility-related elements that contribute to optimal health and quality of life, within the context of successful aging. It then examines the impacts of community design on individual mobility, delving into which traditional and nontraditional actors—including architects, urban planners, transportation engineers, occupational therapists, and housing authorities—play critical roles in ensuring that community environments serve as facilitators (rather than barriers) to mobility. As America ages, mobility challenges for seniors will only increase unless both traditional aging specialists and many nontraditional actors make a concerted effort to address the challenges.